Seric and urinary values for sodium and potassium and electrocardiography parameters in dogs treated with furosemide - Pereira, J. D.G.; Camacho, A. A. [UNESP]; Santana, A. E. [UNESP]; Carvalho, M. B. [UNESP] (My University, 1998)
The serum and urine Na+ and K+ levels and their relationship with electrocardiography characteristics were studied in 15 male adult mongrel dogs, treated twice-a-day with 2, 4, 8mg/kg of live weight doses of furosemide and furosemide associated with KCl during 35 days. Urine samples were analyzed weekly in order to determine the Na+ and K+ concentrations and to evaluate the urinary excretion of both cations. Electrocardiography was performed simultaneously, using limb derivations, speed 50mm/sec and calibration of 1cm corresponding to 1mV. Data showed decreased seric concentrations of Na+ and K+, increase in Na+ fractional excretion between days 7 and 21 of the treatment, slower heart rate and longer PR, QRS and QT intenals in the ECG. Briefly, 2mg/kg furosemide associated with KCl was the most suitable treatment since it induced lesser side effects.
Keywords: Dog; Electrocardiography; Furosemide; Potassium; Sodium